1997
DOI: 10.1038/sj.sc.3100476
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen uptake and heart rate responses during arm vs combined arm/electrically stimulated leg exercise in people with paraplegia

Abstract: The purpose of this study was to compare the oxygen uptake and heart rate responses during submaximal arm cranking to combined arm cranking+electrical stimulation (ES)-induced leg cycling in individuals with spinal cord injury (SCI). Seven subjects with paraplegia (T 4 ± T 12 ) performed combined arm and leg cycling exercise for 5 min, followed by arm cranking alone at the same power output for a further 5 min. During both exercise conditions, steady state oxygen consumption (VO 2 ), carbon dioxide output (VCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 14 publications
(20 reference statements)
0
20
1
Order By: Relevance
“…this is also in contrast to other studies (21)(22)(23)(24), where FES hybrid cycling Vo 2peak has been found to be significantly higher compared with ACE alone. A probable explanation for this may be methodological diversities in terms of lesion levels, determination criteria for Vo 2peak and individual FES training status.…”
Section: Discussioncontrasting
confidence: 55%
“…this is also in contrast to other studies (21)(22)(23)(24), where FES hybrid cycling Vo 2peak has been found to be significantly higher compared with ACE alone. A probable explanation for this may be methodological diversities in terms of lesion levels, determination criteria for Vo 2peak and individual FES training status.…”
Section: Discussioncontrasting
confidence: 55%
“…For instance, results show that a combination of upperbody and ES-LCE exercise, so-called hybrid exercise, can markedly enhance exercise responses [9][10][11]. Even though this technique appears very useful for promoting central cardiovascular and metabolic responses, it will not improve exercise and integrity of the paralyzed legs.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies employing a similar ES muscle recruitment pattern have also documented relatively minor eects on whole body metabolism during concurrent arm cranking exercise (Davis et al 1990;Phillips and Burkett 1995;Hopman et al 1998b). In marked contrast, when ES-induced leg cycling is performed concurrently with arm cranking in PARA, _ V O 2 is higher compared to that measured with arm cranking alone (Raymond et al 1997(Raymond et al , 1999a.…”
Section: Es-induced Leg Muscle Contractionsmentioning
confidence: 52%